VCT clinic HIV burden and its link with HIV care clinic at the University of Gondar hospital - Alemie Getahun; Balcha Shitaye (BMC, 2012)
Abstract Background Voluntary Counselling and Testing (VCT) is an important component of any HIV/AIDS control and prevention activities. VCT makes people aware of their HIV serostatus and enables early identification of those who need care. It is an important link to HIV care and support. The main aim of this study is to describe the HIV burden at VCT and define the relationship between the VCT Center and the HIV Chronic Care Clinic of the University of Gondar (UoG) Hospital. Methods It is a record based descriptive study undertaken by using data collected by health professionals at the VCT center and the HIV chronic care clinic of the UoG Hospital. Patient data collected from 2005/06 to 2008/09 was investigated. Analysis was carried out using the SPSS version 16.0. Results A total of 19,168 people were tested for HIV and a prevalence of 25.4% was obtained. 4298 HIV positive people were referred to the HIV chronic care clinic but only 27% actually registered at the clinic. Chi-square analyses showed residence, age and time of VCT visit showed significant relations with hospital care attendance. Conclusion The overall HIV prevalence is high. The data obtained at the HIV care clinic regarding patients' clinical conditions at acceptance were incomplete. Improvements are required on the link between VCT and HIV care and documentation of data.